Pengaruh Tata Kelola Perusahaan, Kompetensi Auditor Internal dan ESG Terhadap Manajemen Laba: Peran Moderasi Penghindaran Pajak - Nabiilah, Amalia; Hilza Fahira (Publikasi Inspirasi Indonesia, 2024)
This study analyzes the effect of corporate governance, internal auditor competence, and Environmental, Social, and Governance (ESG) on earnings management, by considering the moderating role of tax avoidance. In a competitive business era, companies are required to report reliable financial performance to stakeholders, in accordance with the rules of the Financial Services Authority (OJK) Number 29 / POJK.04 / 2016. However, the pressure to show positive performance often encourages earnings management practices. This study uses quantitative data from the financial statements of banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The results showed that effective corporate governance tends to reduce earnings management practices. Internal auditor competence also plays an important role in reducing earnings manipulation, but its effectiveness decreases when managers engage in tax avoidance. In addition, the implementation of ESG is proven to limit the company's capacity to control profitability. These findings emphasize the importance of strengthening corporate governance and improving internal auditor competence to prevent earnings manipulation.